Analytical modelling of photo-effects on the S-parameters of GaAs MESFETs - Murty Neti.V.L.N.; Jit S. (My University, 2025)
A new analytical model for the photo-dependent S-parameters of GaAs MESFETs has been presented in this paper. The photo-dependent expressions for the gate-source capacitance, gate-drain capacitance, drain-source resistance, domain capacitance, and domain resistance have been derived and used to study the optical effects on the S-parameters of the MESFET. © 2005 Wiley Periodicals, Inc.